Bioluminescence in Polynoid Scale Worms (Annelida: Polynoidae) - Moraes, Gabriela V.; Hannon, Mary Colleen; Soares, Douglas M. M.; Stevani, Cassius V.; Schulze, Anja; Oliveira, Anderson G. (Frontiers in Marine Science, 2021)
Bioluminescence is widespread throughout the phylum Annelida and occurs in terrestrial and marine lineages. Among marine taxa, bioluminescence has been documented in 13 families and anecdotally reported in 6 additional families. Although new bioluminescent systems have been recently described in annelids, there are still many other families whose light emission mechanisms have not been sufficiently studied. Some of these include luminescent species belonging to the Polynoidae family, also known as scale worms, whose iterations of dorsal elytra (scales) have the ability to emit intense light when stimulated. Depending on the degree of stimulation, some polynoids can autotomize these luminous elytra and posterior segments, which could potentially give them an advantage in evading attacks by predators. It is believed that Polynoidae bioluminescence is associated with a membrane enzyme known as “polynoidin”, which was isolated during the early 1980s from Malmgrenia lunulata. However, the characterization and properties of this enzyme, as well as the chemical nature of its substrate or additional potential cofactors, have never been fully described and remain largely unknown. As such, this paper seeks to revisit previous research involving bioluminescence studies in Polynoidae, as well as the morphological, phylogenetic and ecological aspects related to this emission of light.